Fresh water Ascomycetes from North Maharashtra-II - Patil, S Y; Borse, B D (Current Botany, 2013)
The present paper deals with three species of freshwater ascomycetes viz. Caryospora putamium (Schw.) de Notaris ,Natantispora retorquens (Shearer and Crane) Campb. ,Anderson and Shearer and Panorbis viscosus (Schmidt) Campb., Anderson and Shearer were collected from the submerged wood samples from the various water bodies in North Maharashtra region. All the three species are being recorded for the first time form North Maharashtra. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.